PENGARUH MODEL PEMBELAJARAN RECIPROCAL TEACHING TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN BAHASA INDONESIA SDN 060921 MEDAN SUNGGAL - Laura Anatasya Surbakti; Rumiris Lumban Gaol; Reflina Sinaga; Darinda Sofia Tanjung; Dyan Wulan Sari HS; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this study is the low learning outcomes Indonesian grade IV students of SD Negeri 060921 Medan Sunggal. The purpose of this study is to determine the influence of the reciprocal teaching model on the learning outcomes of grade IV students. This type of research is quantitative research. with a research method, namely experimental research. The population is 30 students and the sample is saturated. Data collection techniques are carried out by non-test techniques (observation and documentation) and test techniques. Based on the results of the study, it was shown that there was an influence of the reciprocal teaching learning model on the learning outcomes of grade IV students of SD Negeri 060921 Medan from the correlation coefficient test of 0,606 0,361 Therefore, it was concluded that the alternative hypothesis (Ha) was accepted, where there was a positive and significant influence between the use of the reciprocal teaching learning model on student learning outcomes, judging from the results of hypothesis testing obtained data 4,027 and of 2,048. The comparison shows > yaitu 4,027 > 2,048 means Ha is accepted. There is a Significant Influence on theInfluence of the Reciprocal Teaching Learning Model on the Learning Outcomes of Grade IV Students in Subject Indonesian SDN 060921 Medan Sunggal Tahun Plearning 2024/2025.